Functional and morphological correlates of developmental dyslexia: A multimodal investigation of the ventral occipitotemporal cortex. Issue 5 (11th June 2021) - Borghesani, Valentina; Wang, Cheng; Watson, Christa; Bouhali, Florence; Caverzasi, Eduardo; Battistella, Giovanni; Bogley, Rian; Yabut, Nicole A.; Deleon, Jessica; Miller, Zachary A.; Hoeft, Fumiko; Mandelli, Maria Luisa; et al.
ABSTRACT: Background and Purpose: The ventral occipitotemporal cortex (vOT) is a region crucial for reading acquisition through selective tuning to printed words. Developmental dyslexia is a disorder of reading with underlying neurobiological bases often associated with atypical neural responses to printed words. Previous studies have discovered anomalous structural development and function of the vOT in individuals with dyslexia. However, it remains unclear if or how structural abnormalities relate to functional alterations. Methods: In this study, we acquired structural, functional (words and faces processing), and diffusion MRI data from 26 children with dyslexia (average age = 10.4 ± 2.0 years) and 14 age‐matched typically developing readers (average age = 10.4 ± 1.6 years). Morphological indices of local gyrification, neurite density (i.e., dendritic arborization structure), and orientation dispersion (i.e., dendritic arborization orientation) were analyzed within the vOT region that showed preferential activation in typically developing readers for words (as compared to face stimuli). Results: The two cohorts diverged significantly in both functional and structural measures. Compared to typically developing controls, children with dyslexia did not show selectivity for words in the left vOT (contrast: words > false fonts). This lack of tuning to printed words was associated with greater neurite dispersion heterogeneity in the dyslexia cohort, but similar neurite density. These group differences were not present in the homologous contralateral area, the right vOT. Conclusions: Our findings provide new insight into the neurobiology of the lack of vOT word tuning in dyslexia by linking behavior, alterations in functional activation, and neurite organization.